Association between platelet-to-albumin ratio and total spine bone mineral density in older adults with thoracolumbar fragility fractures: a retrospective cross-sectional study - He, Xinhuan; Yin, Weicong; Huang, Dixi; Chen, Chuqun; Lai, Weiqiang; Hu, Siyuan; Li, Xu; Gong, Kaiqin; He, Kunrui; Liu, Weile; Huang, Shoubin; Zheng, Shaowei; et al. (Frontiers in Endocrinology, 2026)
BackgroundGlobal aging elevates the incidence of thoracolumbar fragility fractures (TLFFs), which are linked to osteoporosis. Platelets (PLT) and albumin influence bone health; the platelet-to-albumin ratio (PAR) is applied in multi-disease research, but it has not yet been applied to patients with TLFF. This study thus explores PAR’s association with bone mineral density (BMD).MethodsThis retrospective cross-sectional analysis based on a cohort of TLFF patients included 703 elderly TLFF patients from Huizhou First Hospital (2020–2025). BMD was measured, PAR calculated, and grouped; covariates were collected. Subsequently, characterization of the study population, univariate linear regression analyses, and subgroup as well as interaction analyses were carried out.ResultsHigh-PAR groups had higher PLT, lower albumin, and lower BMD. PAR showed a significant negative association with total spine BMD (TS-BMD) even after adjustment; the initial association of neutrophill-to-albumin ratio (NPAR) became non-significant post-adjustment.ConclusionIn elderly TLFF patients, PAR is negatively associated with TS-BMD. As an easily measurable index, PAR may act as a clinical tool.